2023
DOI: 10.1039/d2sc06982b
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the high-brightness “warm” white light emission of two-dimensional perovskite crystalsviaa pressure-inhibited nonradiative transition

Abstract: Efficient warm white-light emission is an urgently ideal characteristic of single-component materials for light-emitting applications. Although two-dimension hybrid perovskites are promising candidates for light-emitting diodes, as it possesses broadband self-trapped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Similar to previously reported work, the broadband emission with a large Stokes shift, wide FWHM and long lifetime should originate from the radiative recombination of STEs due to the strong electron–phonon (EP) coupling effect in the deformable 0D soft crystal lattice. 28,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to previously reported work, the broadband emission with a large Stokes shift, wide FWHM and long lifetime should originate from the radiative recombination of STEs due to the strong electron–phonon (EP) coupling effect in the deformable 0D soft crystal lattice. 28,29…”
Section: Resultsmentioning
confidence: 99%
“…The soft crystal lattice readily vibrates with photo-induced excitons as strong electron–phonon coupling, resulting in largely Stokes-shifted broadband light emission. 28,29 As a consequence, these 0D hybrid metal halides can be utilized as down-conversion single-component white light phosphors to fabricate LEDs such as (HMTA) 4 PbMn 0.69 Sn 0.31 Br 8 , [Bmim] 2 SbCl 5 , etc. 30,31 More significantly, some 0D hybrid metal halides have been further explored as X-ray scintillators with impressive light yield under X-ray excitation due to high PLQY and large Stokes shift.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Above 14.2 GPa, non‐radiative decay channel dominates, causing a quenching of the emission intensity. [ 25 ] Further studies are required to clarify the mechanisms of the PIEE observed in coronene. The fit results obtained at each pressure are summarized in Table S4 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We then calculated the radiative decay rate constants (k r ) and non-radiative decay rate constants (k nr ) for the three Schiff base complexes using quantum yields and fluorescence lifetimes (Table 1) [36]. It can be seen that as the pH increased from 5.0 to 7.0, the k r values of Zn-3,5-Cl-saldmpn and Zn-3,5-Br-saldmpn both increased, while the k nr values decreased, which implied that the transmission efficiency of the emitted light was enhanced because the energy of the excitation light was more easily dispersed into radiative energy [37]. It should be noted that under the same pH conditions, the k nr value of Zn-3,5-Br-saldmpn was much larger than that of Zn-3,5-Cl-saldmpn, which may have been caused by the heavy atom effect [38].…”
Section: Sensing Mechanismmentioning
confidence: 97%